Acute effects of repeated sprints on performance measures during the countermovement rebound jump - Xu, J.; Turner, A.; Jordan, M. J.; Comyns, T. M.; Chavda, S.; Bishop, C. (The Journal of Strength and Conditioning Research, 2025)
The countermovement rebound jump (CMRJ) test is an alternative to traditional jump assessments, providing unique insights into slow and fast stretch-shortening cycle mechanics. This study investigated the effects of repeated sprint-induced fatigue (4 sets of 6 × 40-m sprints with 20-second interrepetition rest) on CMRJ performance metrics, including jump heights, time to takeoff, ground contact time, reactive strength index modified (RSImod), RSI, countermovement depth, and leg stiffness, measured at baseline, during sprints, and over a 24-hour recovery period. Twenty-four, elite, male, team-sport athletes completed CMRJ tests before and after each sprint set, with additional assessments at 0.5-, 1-, and 24-hour postsprints. Results showed significant reductions in CMRJ heights, RSImod, and RSI immediately following sprints (effect size [ES] = 0.27-1.78, p = 0.040), indicating acute decrements in jump performance. Strategy-based metrics, such as leg stiffness and contact times, remained stable (ES = 0.09-0.57, p = 0.079), suggesting limited sensitivity to fatigue. These findings support the use of CMRJ outcome metrics to evaluate neuromuscular fatigue effectively in an athlete population with a noninvasive solution suitable for field settings.